Cardiac magnetic resonance imaging detects subclinical right ventricular impairment in systemic sclerosis - Bezante, Gian Paolo; Rollando, Daniela; Sessarego, Marta; Panico, Nicoletta; Setti, Maurizio; Filaci, Gilberto; Molinari, Giuseppe; Balbi, Manrico; Cutolo, Maurizio; Barsotti, Antonio; Indiveri, Francesco; Ghio, Massimo (Journal of rheumatology, 2007)
To assess myocardial involvement in patients with systemic sclerosis (SSc) with no signs or symptoms of cardiac impairment (New York Heart Association functional class I). Fifty patients (45 women, 5 men, age 53.3 +/- 12.9 yrs) who did not complain of serious diseases other than SSc were recruited out of 119 consecutive patients with SSc. Thirty-three were found to have limited cutaneous SSc (lSSc) and 17 diffuse SSc (dSSc). All underwent cardiovascular magnetic resonance imaging (MRI) to determine right and left systolic and diastolic volumes and ventricular ejection fractions (RVEF and LVEF). Thirty-one healthy subjects matched for sex, age, and body surface area (BSA) were studied as controls. Diffusion lung capacity test (DLCO) and high resolution computed tomography were performed to evaluate lung involvement. Disease duration between patients with lSSc (14.1 +/- 11.4 yrs) and those with dSSc (6.9 +/-4.4yrs) was found to be significantly different (p < 0.003). lSSc patients were older than those with dSSc (54.8 +/- 13.7 yrs vs 50.4 +/- 9.9 yrs, respectively; p < 0.04). Anticentromere antibodies and Scl-70 were positive in 23 (46%) and 17 patients (34%). Except for the left and right systolic volumes, all unadjusted cardiac MRI measures were significantly reduced in SSc compared to the controls (p < 0.001 and p < 0.009). These differences persisted after adjustment for subjects' height and BSA. Raw RVEF data and RVEF data matched for height and BSA were significantly reduced in dSSc patients in comparison to lSSc (p < 0.03). Compromised RVF was found in patients with asymptomatic SSc. Unlike standard diagnostic techniques, cardiac MRI appears to be a rapid and noninvasive means of determining subclinical right myocardial involvement that is otherwise undetected in patients with SSc.